Akseptasi Kurikulum Merdeka dan Implikasinya terhadap Demoralisasi Siswa Pendidikan Dasar - Vita Fitriatul Ulya; Ahmad Suyanto (SITTAH: Journal of Primary Education, 2025)
The increasing undisciplined behavior, low responsibility, and decreasing social empathy among elementary school students signify demoralization. This study aims to analyze the acceptance of the Merdeka Curriculum and its implications for demoralization at the elementary school level. This study used a descriptive qualitative method. The study subjects included the principal, teachers, students, and parents of students at MI Bahrul Ulum Binangun and SDI Al-Hadad in Singgahan District, Tuban Regency, East Java. The results showed that acceptance of the Merdeka Curriculum was quite diverse. Teachers at SDI Al-Haddad and MI Bahrul Ulum welcomed the flexibility and differentiation learning approach, although they still had difficulty optimally implementing project-based learning strategies. Students showed increased involvement in learning, especially in activities that foster creativity and collaboration. The Merdeka Curriculum positively contributed to reducing indications of student demoralization, especially by instilling the values ​​of independence, responsibility, and mutual cooperation. In its implementation, the effectiveness of this curriculum is greatly influenced by teacher readiness, adequate training, and support from the school and family environment.